A Reflection of Culture of Equality and Inequality: Body, Security and the Issue of Survival for Pakhtun Woman in Pakhtunwali - Abu Hurara (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The article seeks to expand the realm of Pakhtun woman, her manifested position and awakens fresh possibilities with regard to the explanation of the outside forces towards women in Pakhtunwali. It presents an analysis, where the phrase ‘the outsider is personal’ is used for a reflection of culture of equality and inequality of Pakhtun women in the context of Pakhtunwali. In the basic principles of Pakhtunwali, it explores the Pakhtun woman, her body, security and the issue of survival as a personal identity. How Pakhtun women express her personal self-definition and how woman conceives herself as having relations to the outside forces? Why and how the outsider is the source of power and social control in the gender hierarchy of Pakhtunwali? To understand the manifestation of Pakhtuns woman, this article also explores the concept of ‘a taboo of protection’ by examining how a woman’s identity is symbolized by her nature, which encompasses her body, mind, and gender, while critically analyzing the cultural interpretations that shape these elements.